Symbolism and description of tiger in Mongolian folklore - Ganbold, Batmunkh (Studia Folclorica, 2024)
This article tells about description and status of tiger which are assumed as ones of the four leviathans in Mongolian folklore and literary culture. For this the article not only dealt with epics, myths, tales, riddles, and proverbs but also Mongolian traditional land examining custom. There are full of roles and symbol isms of tiger in Mongolian literary culture, customs, and folklore. Tiger is deeply absorbed in literary culture than other animals that feeds Mongolians and have a significant impact on his lives. That is why it is interesting although tiger do not live in Mongolia. To clarify the reason of how they become part of Mongolian literary culture we should consider the issue in connection to the symbolism of “four leviathans”. There is a vital notion in oriental culture is the conjunction of symbols and de scription of the “four leviathans”. Originated place and date of this notion is not fixed but there are many hypothesizes and proposals. The most popular explanation is the following: Initially the myth roles named asuri, tengri, dragon are formed in mentality of Orientals after that the concept was born which expressed upper world, middle world, and lower world. There are two leviathans each in upper world and also middle world separately. Then altogether they called “four leviathans”. The myths were originated from India and China. The two leviathans in upperworld among the “four leviathans” are named dragon and garuda. The lion and tiger are leviathans of middle world which do not live in our country. Considering the roles of the tiger in Mongolian folklore, the epic named “Erkhiidee erchtei Eriin sain Khambuudai mergen khan” it is said as following: “Manglai čaɣan arslan Mal-i ni toɣurin (toɣlaǰu) Qatun bars-un ǰulǰaɣ-a Qatun-I toɣurin (toɣlaǰu) ǰeg d lebe gen-e”. It means ruling the tiger is a symbol of the ability to repress evil. Further in a Mongolian epic the lion is described: “Baɣan-a tal-a-du ni bars arslan Baǰaɣaldaulun seyilügsen Dalan tabun teremetei bayidaɣ Dalan ɣurban unitai bayidaɣ” “Aduučin sayin aɣ saqal ebügen Aba-a aq-a ni aru-du ergiged Arban ǰil-dü ködülgedüi Arslan čaɣan Abdar-a-yin čooǰi-yi multuluad” Clarified the behavoirs of its great power and rapid physique. Mонгол аман зохиол дахь барын дүр, бэлгэдэл Хураангуй: Өгүүлэлд ертөнцийн дөрвөн хүчтэний нэг болох барыг монгол аман зохиол, утга соёлд хэрхэн дүрсэлж ирснийг жишээгээр тодруулж, өнөөдөр бидний үед тэрхүү уламжлал хэрхэн хадгалагдаж буйг өгүүлэв. Чингэхдээ тууль, домог, үлгэр, оньсого, зүйр цэцэн үг зэрэг аман зохиолын төрөл зүйлсэд барын дүрийг хэрхэн дүрсэлснийг тодруулж, монголчуудын уламжлалт ан ав, зүүд, зүгийн бэлгэдэл, газар шинжих ёс зэрэгтэй харьцуулан тэдгээрийн утга бэлгэдлийг тайлан тайлбарласан байна. Түлхүүр үг: аман зохиол, дөрвөн хүчтэн, дүрийн судалгаа, сүр хүч